Electrostatic theory of charged particle polarisation: applications in self-assembly, pharmaceutical and atmospheric processes - Baptiste, Joshua (2021)
New developments in theoretical approaches to calculating electrostatic interactions between charged polarisable particles are presented and applied to a wide range of charged systems to test the versatility of the solution. Here, the theory behind the expansion of the many-body polarisable electrostatic solution (Lindgren et al., 2018) has been expanded to include non-homogeneous surface charge densities in the form of point charges, and also the introduction of external electric fields. A wide range of trends are explored, along with testing of the implementation of this new development. The model is then applied to applications that test the model against a wide range of experimental data, including: the atmospheric physics involved with cloud formation in the upper atmosphere; the aggregation of bipolar pharmaceutical aerosols found in dry powder inhalers; the self-assembly behaviour of bipatchy microcolloids; and the study of the role of counterions in the spontaneous formation of dimers between hydrophilic macroanions in solution. The model displays its robustness not only by providing solutions to problems on multiple length-scales (nano- and meso-scale in this work), but it also handles a range of mediums with both systems in solution and in vacuum/air are studied. The work is finally concluded, with a host of scenarios provided as possible future work.